2017
DOI: 10.1002/glia.23283
|View full text |Cite
|
Sign up to set email alerts
|

Brain metabolic sensing and metabolic signaling at the level of an astrocyte

Abstract: Astrocytes support neuronal function by providing essential structural and nutritional support, neurotransmitter trafficking and recycling and may also contribute to brain information processing. In this article we review published results and report new data suggesting that astrocytes function as versatile metabolic sensors of central nervous system (CNS) milieu and play an important role in the maintenance of brain metabolic homeostasis. We discuss anatomical and functional features of astrocytes that allow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 107 publications
(84 citation statements)
references
References 131 publications
2
77
0
5
Order By: Relevance
“…Fine astrocytic processes are closely associated with pre‐ and post‐synaptic neurons to form tripartite synapses (Araque, Parpura, Sanzgiri, & Haydon, ; Halassa et al, ; Perea, Navarrete, & Araque, ; Santello, Calì, & Bezzi, ), potentially modulating synaptic signaling and plasticity. Astroglial signaling has been shown to modulate activities of autonomic and respiratory circuits in several regions of the brainstem containing functionally distinct neural networks including the preBötC (Forsberg et al, ; Sheikhbahaei et al, ), RTN (Erlichman & Leiter, ; Gourine et al, ; Huckstepp et al, ; Mulkey & Wenker, ; Wenker, Sobrinho, Takakura, Moreira, & Mulkey, ), rostral ventrolateral medulla (Marina et al, ) and NTS (Accorsi‐Mendonça, Zoccal, Bonagamba, & Machado, ; Funk et al, ). While it has been proposed that astrocytes may have neural circuit‐specific structural and functional properties (Chai et al, ), the morphological features of astrocytes residing in functionally distinct brainstem respiratory regions have not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…Fine astrocytic processes are closely associated with pre‐ and post‐synaptic neurons to form tripartite synapses (Araque, Parpura, Sanzgiri, & Haydon, ; Halassa et al, ; Perea, Navarrete, & Araque, ; Santello, Calì, & Bezzi, ), potentially modulating synaptic signaling and plasticity. Astroglial signaling has been shown to modulate activities of autonomic and respiratory circuits in several regions of the brainstem containing functionally distinct neural networks including the preBötC (Forsberg et al, ; Sheikhbahaei et al, ), RTN (Erlichman & Leiter, ; Gourine et al, ; Huckstepp et al, ; Mulkey & Wenker, ; Wenker, Sobrinho, Takakura, Moreira, & Mulkey, ), rostral ventrolateral medulla (Marina et al, ) and NTS (Accorsi‐Mendonça, Zoccal, Bonagamba, & Machado, ; Funk et al, ). While it has been proposed that astrocytes may have neural circuit‐specific structural and functional properties (Chai et al, ), the morphological features of astrocytes residing in functionally distinct brainstem respiratory regions have not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the effects of an unhealthy, over nutritious high‐fat and/or high‐sugar diet on brain functioning, and the involvement of astrocytes has received considerable attention. These studies mostly focused on hypothalamic astrocytes, as they are key in detecting alterations in metabolic parameters and hormonal changes (e.g., leptin and ghrelin) related to the energy status of the brain (Buckman & Ellacott, ; García‐Cáceres et al, ; Marina et al, ), and have been shown to control food intake (Buckman et al, ; Parsons & Hirasawa, ; Yang, Qi, & Yang, ). To study the effects of an early unhealthy diet, a model of maternal high‐fat diet (HFD) is commonly used.…”
Section: Ela Induced Alterations In Astrocytesmentioning
confidence: 99%
“…A recent review by Marina and colleagues has detailed how researchers have tackled the astrocyte hypothesis by blocking ATP‐mediated signalling, which leads to slow progression of cardiac remodelling in rats and reduced systemic blood pressure in hypertensive rats (Marina et al. ). The role of glia and purinergic signalling will be discussed in more detail in the next section.…”
Section: Introductionmentioning
confidence: 99%